A Real option approach to valuating infrastructure investments - Lee, Hyuk (KDI School, 2011)
A correct methodology for valuing an infrastructure investment is essential to both of two parties, government and private concessionaires, in order to allocate the project risks reasonably and fairly and makes the project successful. Real Option Analysis (ROA) can be a good approach for appropriately valuing an infrastructure investment because it can capture the "uncertainties of the project and flexible managerial strategies" (Dixit, and Pindiyck, 1994) during the investment horizon by using option pricing model. This study investigated the value of project using DCF method and ROA approach, the cause of the gap, and project value from ROA approach when adding government guarantees such as MRG and the option to abandon. Additionally, this paper identified how the project value from ROA approach would change when variable assumptions were adjusted. In conclusion, what these results can suggest to the policy makers was covered.
Thesis(Master) --KDI School:Master of Public Policy,2011